Time Analysis for BPMN Gateways Using Queuing Theory. - SAHEB, MAHMOUD (Information Technology Journal, 2013)
Business process modeling is an important phase of business process management phases. One of the steps needed to enhance a business process model is analyzing the timing and the queuing behavior. Currently Business Process Management connected directly with information technology, either by automating some of the tasks, or by simulating the process for understanding and enhancing. This paper presents an analytical approach to analyze the business process models using queuing systems classifications for the basic BPMN2 gateways as M/M/1, M/M/c and M/D/1. Five types of the BPMN gateways have been analyzed depending on their specifications to define the inflow and the outflow and the probability producing and consuming tokens. An algorithm for computing arrival rate and average waiting time, and illustrative example for our methodology has been presented.
Keywords: Research Subject Categories::TECHNOLOGY; BPMN; business process modeling; queuing; time analysis; Simulation